The health promoting sports coach: theoretical background and practical guidance - Benjamin Tézier; Kévin Barros; Susanna Geidne; Farid Bardid; Spartaco Grieco; Stacey Johnson; Sami Kokko; Barry Lambe; Arthur Lefebvre; Aoife Lane; Linda Ooms; Jan Seghers; et al. (BMC Sports Science, Medicine and Rehabilitation)
Abstract The sports club setting is a key context for health promotion, but it can also be associated with risky behaviours. Sports coaches play a crucial role in supporting the physical, mental and social health of sport participants but often lack the resources and support to do so. This paper proposes a guide to help coaches become health promoters by aligning their actions with the Health Promoting Sports Club model, which represents the setting-based approach applied to sports clubs. An embedded mixed-method study with a QUAL (qual) design was used, where 15 experts took part in 5 meetings and 299 coaches provided input through an online survey. Four steps were carried out: (1) defining the health-promoting sports coach and key action principles, (2) co-constructing progression stages using the settings-based approach, (3) identifying key actions for promoting health in different moments of coaching (i.e., before, during, and after training and competition, and outside of coaching), and (4) developing long-term intervention components. A definition of the health-promoting sports coach was produced, and eight key action principles have been identified, divided into three dimensions: connection with the system, adoption of a coaching philosophy, and focus on participants. Five stages of progression for integrating health promotion into coaching have been established, ranging from risk prevention to a global approach involving the entire sports system. Specific actions for each moment of coaching (before, during, and after training and competition, and outside of coaching) have been identified, such as monitoring the physical, mental, and social health of participants or plan the coaching session to ensure safety, inclusion, and well-being for all sports participants, staying open for last-minute changes. Finally, long-term intervention components to support the implementation of these actions in practice have been developed, based on what coaches are already doing, the skills they possess and the five stages of progression. This paper enables the development of a guide to help sports coaches promote health by identifying concrete actions and short- and long-term interventions, whilst making links with the health promoting sports club model. It broadens the scope of coaching by incorporating health principles, while emphasising the need to adapt to the environment and context of the club. This work calls for future research to test the effectiveness and feasibility of these approaches in various sporting environments.